1990
DOI: 10.1103/physrevc.42.2180
|View full text |Cite
|
Sign up to set email alerts
|

Elastic Coulomb scattering of heavy ions at intermediate energies

Abstract: Relativistic effects in two-body Coulomb collisions are investigated within a classical context. Special emphasis is given to heavy-ion collisions at intermediate energies. It is found that such corrections may be responsible for a 10 -20% increase of the elastic cross sections for a fixed scattering angle and kinetic energy. Comparisons with other methods are also made and some useful simple parametrizations of the cross sections are obtained. The separate contributions from kinematic and retardation correcti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(42 citation statements)
references
References 8 publications
2
40
0
Order By: Relevance
“…Explicit expressions for these Lagrangians are given in ref. [2]. The authors show that the scattering angle increases by up to 6% when relativistic corrections are included in 208 Pb + 208 Pb collisions at 100 MeV/nucleon.…”
Section: Semiclassical Methods and Elastic Scatteringmentioning
confidence: 98%
See 1 more Smart Citation
“…Explicit expressions for these Lagrangians are given in ref. [2]. The authors show that the scattering angle increases by up to 6% when relativistic corrections are included in 208 Pb + 208 Pb collisions at 100 MeV/nucleon.…”
Section: Semiclassical Methods and Elastic Scatteringmentioning
confidence: 98%
“…This has been investigated in ref. [2]. A system of two point charges interacting electromagnetically and moving at low velocities can be described by an approximate Lagrangian which depends only on the degrees of freedom of the particles neglecting those related to the electromagnetic field (the Darwin Lagrangian's).…”
Section: Semiclassical Methods and Elastic Scatteringmentioning
confidence: 99%
“…[16] for a discussion of relativistic corrections of the Rutherford cross sections, not considered here. Our results for 12 C+ 12 C scattering are compared to experimental data at bombarding energies of 85 MeV/nucleon [17].…”
Section: Resultsmentioning
confidence: 99%
“…[25]. It was shown that the scattering angle increases by up to 6% when relativistic corrections are included in nuclear collisions at 100 MeV/nucleon.…”
Section: Intermediate Energy Coulomb Excitationmentioning
confidence: 99%